Five points on columns - Rockland, Kathleen S. (Frontiers in Neuroanatomy, 2010)
“Column,” like “gene,” has both conceptual and linguistic shortcomings. The simple question “what is a column” is not easy to answer and the word itself is not easy to replace. In the present article, I have selected five points, in no way comprehensive or canonical, but which may nevertheless serve as a prompt and aid for further discussions and re-evaluation. These are: that anatomical columns are not solid structures, that they are part of locally interdigitating systems, that any delimited column also participates in a widely distributed network, that columns are not an obligatory cortical feature, and that columns (as “modules”) occur widely in the brain in non-cortical structures. I focus on the larger scale macrocolumns, mainly from an anatomical perspective. My position is that cortical organization is inherently dynamic and likely to incorporate multiple processing styles. One can speculate that the distributed mappings within areas like piriform cortex may resemble at least one mode of neocortical processing strategy.